ISLAMIC FAMILY LAW AND PUBLIC EDUCATION ON CRYPTOCURRENCY: A FRAMEWORK FOR COMPLIANCE AND AWARENESS - Ruchmana, Riza; Muhasim; Sado, Arino Bemi (Jurnal Ilmiah Pendidikan Citra Bakti, 2024)
Public education about cryptocurrency within the Muslim community is still limited, with many individuals not understanding the potential benefits and associated risks. This creates a significant knowledge gap in the context of Islamic family law. This study aims to enhance understanding of cryptocurrency through a public education approach focused on the perspective of Islamic family law. The methodology employed in this research is a literature review, analyzing various literature, articles, and guidelines from religious authorities and Islamic finance experts. The results indicate that the majority of the Muslim community has not received adequate education regarding cryptocurrency, hindering their ability to invest wisely. Effective public education can improve public understanding and awareness of the benefits and risks of cryptocurrency, ensuring its use complies with Islamic law principles. These findings highlight the importance of support from religious authorities and Islamic finance experts in providing accurate and relevant guidance. With a holistic and structured approach, public education can help Muslims make better decisions regarding investment and the use of cryptocurrency in their daily lives.